Organic Animal Products in the EU to Support Sustainable Consumption - Szubska, Natalia (Comparative Economic Research. Central and Eastern Europe, 2025)
A critical analysis of the research discourse on the development of organic farming is imperative if it is to contribute to the spread of sustainable consumption patterns, as indicated in the European Green Deal (EGD). However, there is a notable dearth of research from a macroeconomic perspective. What and how much we consume affects human health and the environment. Therefore, there is a need to increase consumer awareness of the consequences of food choices, as organic animal products can contribute to sustainable consumption and production. The study aims to determine the level of development of the production of organic animal products in European Union (EU) countries. Synthetic indicators of the development level of EU countries in 2016 and 2020 were constructed based on the Principal Components Approach (PCA) using Eurostat data. A survey and literature review shows that countries at the top of the ranking, such as Denmark, Sweden, Finland and Austria, have active policies to support the development of organic agriculture on both the supply and demand sides. On the other hand, a divergence in the factors that influence the development of organic agriculture was also observed in the top-ranked countries. Therefore, the development of organic agricultural production, including organic animal products, requires the diffusion of experiences across the EU to support the multifaceted OAFR (organic agriculture and food research) paradigm and the Sustainable Development Goals.